A ANALISIS DAYA PEMBEDA DAN TINGKAT KESUKARAN SOAL BAHASA ARAB DI MADRASAH TSANAWIYAH NEGERI KOTA CIMAHI - Agus Gunawan (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
This study aims to analyse the discriminating power and level of difficulty of evaluation questions in Arabic lessons for Year 9 students at the State Islamic Junior High School (MTsN) in Cimahi City for the 2024-2025 academic year. The research data was taken from the results of formative tests of 9th grade students with 20 multiple-choice questions. The analysis was carried out using two item analysis approaches, namely analysis of the discriminating power and level of difficulty of the questions. Each item was analysed to determine its discriminating power and level of difficulty. Discrimination index calculation was performed to assess the ability of questions to distinguish between high- and low-ability students, while difficulty level was calculated to determine how difficult or easy the questions were for students. The research results indicate that students' understanding and motivation can be determined through the difficulty level of questions created by teachers. This has implications for teachers' lesson preparation, as they should prepare better questions before giving them to students, especially gifted students.